Variable Number Tandem Repeats (VNTR) MAOA Gene Promoter Polymorphism Association with Adolescent Delinquency in Bali: A Preliminary Study - Anak Ayu Sri Wahyuni (Journal of Global Pharma Technology, 2018)
Background: One of the genes that concern behavioral problems is the MAOA. Animal studies have shown that increased dopaminergic and noradrenergic function is associated with aggressive behavior. It is therefore obvious that any change in the catabolism function possessed by MAOA can lead to aggressive behavior. Individuals with decreased or increased MAOA function in most cases had a 30 bps of VNTR (Variable Number Tandem Repeat) polymorphism on the MAOA gene promoter. Children with 3R or 5R alleles are more likely to develop into violent behavior than those with alleles of 3.5R or 4R. Aim: The study aims to determine the proportion of VNTR polymorphism of MAOA gene promoter with juvenile delinquency in Bali and the relationship between VNTR polymorphism of MAOA gene promoter with juvenile delinquency in Bali. Method: The populations in this study were adolescents (12-18 years old) divided into case and control group matched by age and sex. Participants were asked to provide a blood sample for DNA extraction. The analysis on MAOA data cannot be conducted because the outgoing data is a constant. Result: All samples in the group had a high activity (100%) and only two samples (4.6%) had heterozygous genotyping, as well as the statistical analysis, could not be performed. Conclusion: This study has not been able to answer the hypothesis, because it was unable to be analyzed. The analysis cannot be fixed because all the measurements obtained are homogeneous.Keywords: Variable Number Tandem Repeats (VNTR), MAOA, Delinquency.